BIROKRASI DAN POLITIK: NETRALITAS PERANGKAT DESA DALAM PEMILIHAN KEPALA DESA SITIMERTO KECAMATAN PAGU KABUPATEN KEDIRI TAHUN 2016 - Endik Hidayat; Miskan (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
Increased political participation of the village community after the reformation, marked by increasing interest in the community to run for village head elections and village decision-making. Increasing village community participation certainly has hope that the neutrality of bureaucracy is maintained at the village level. So that the climate of political contestation at the village level runs ideally in accordance with the values of democratic life. The purpose of this research is to find out the role of bureaucracy politicization in winning candidate village head Aditya Dimas in Pilkades simultaneously December 26, 2016. Then, knowing the factors that cause political behavior are not neutral village officials and forms of violations in contestation Pilkades Sitimerto December 26 2016. This research using qualitative research methods with a case study approach. The selection of qualitative methods with a case study approach was carried out because there were distinctive characteristics in the election of the head of the Sitimerto village in Kediri Regency. The results of this study show, firstly, that the practice of neutrality in village bureaucracy in the Sitimerto village case is not proven, that the village apparatus is not neutral in the village head election. Second, the factors that motivate village officials to be non-neutral in the case of the Sitimerto village head election are the widespread use of money politics as an attraction for material benefits to the village apparatus and political dinasty of incumbent. Third, a number of forms of violations of neutrality that occurred in the case of the election of the Sitimerto village head were proven that the village officials acted as cadres of the incumbent candidates and participated in distributing money politics to the villagers.